Kegiatan Dan Pendapatan Usahatani Seledri (Apium gravioles L) Di Desa Saring Sei Binjai Kecamatan Kusan Hilir Kabupaten Tanah Bumbu Provinsi Kalimantan Selatan - Bahrun Bahrun (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
The effect of this research to know management / celery farming management is sighted from technical aspect and to know big cost, acceptance and income of celery farming at Silvan Sei Binjai's Filter. This research utilize survey method with tech observation.  Respondent determination to be done census ala of 10 farmers which labour celery farmings. Acceptance average as big as Rp. 6. 980. 000,00 / farmer.  Averagely propertied as big as 6.617.309,17 / farmers.